Perpetuating traditional influences: voluntary disclosure in Malaysia following the economic crisis - Mohd Ghazali, Nazli Anum; Weetman, Pauline (Elsevier, 2006)
Prior research on listed companies in Malaysia, Hong Kong and Singapore during and before the 1997 financial crisis has reported a significant association between ownership structure and the extent of voluntary disclosure in annual reports. We examine data for Malaysia after the 1997 financial crisis to assess whether the regulatory reaction to the crisis increased the awareness of disclosure as a tool of corporate governance and reduced the influence of insider domination on voluntary disclosure. We contrast director ownership and government ownership as determinants of voluntary disclosure in Malaysian company annual reports. Additionally we include consideration of proprietary costs by testing whether industry competitiveness has an impact on voluntary disclosure.